Aspectos da tessitura do texto à luz da linguística textual - Ciríaco, Maria Inês Francisca (2020)
Situated within the realm of research into “Methods of establishing discourse and text meanings”, this thesis has as its main theme the aspects of text construction. Its general objective is the recognizing of the textualization processes, which conduct textuality, taking into consideration its constituent parts and the relationships they establish. Specific objectives include: the comprehension of the constitution and development of Text Linguistics; the conception of text and discourse from the perspective of Text Linguistics; the reflection about the controversy between the concepts of discursive and textual genre; the development of a proposal for textual analysis, which will be used to direct the study of our corpus and which may be applied by other researchers and professors in their work inside and outside the university; the investigation of the selected corpus and the relations established in the textual structure by means of the textual components and contextualizers; and the verification, by means of analysis, of the relation between text and context. For this, the following hypotheses were formulated: can it be considered that the text only constitutes itself in a clear and cohesive way if all structural elements, which involve the linguistic framework necessary for its comprehension as an object of communication, are contemplated? Is Text Linguistics adequately suited for the analysis of linguistic processes for the constitution of texts, as well as the interaction relations between the author, interlocutor and context? The selected corpus consists of four texts by authors from different official spaces of the Portuguese language, whose theme is related to linguistic aspects: Descascar palavras by Manoel de Barros (1989) and Abraço caudaloso by Gregório Duvivier (2015), from Brazil; Bibliotecas by Valter Hugo Mãe (2018), from Angola; and Perguntas à língua portuguesa by Mia Couto (2011), from Mozambique. The method used was the bibliographic search. The approach utilized based on the studies developed by Adam (2017; 2019 [2017]; Antunes (2005; 2006 [2010]; 2017); Beaugrande e Dressler (1997 [1983]); Bernárdez (1982); Fávero e Koch (2012 [1983]); Guimarães (1992; 2013); Koch (2015 [2004]); Marcuschi (2012 [1983]; 2014 [2008]; 2010 [2002]); Sautchuk (2003); e Van Dijk (1997 [1983]). The results demonstrate the relevance of the Postulates of Textual Linguistics in effect until now but signal the need to reconsider the definition of coherence, as Koch (2015 [2004]) already signals, which should not be addressed as a standard of textuality, but the result that is achieved through other textual aspects.